2007
DOI: 10.1021/jm0703901
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibition of Mycobacterium bovis, Mycobacterium tuberculosis and Mycobacterium avium In Vitro:  Effect of 1-β-d-2‘-Arabinofuranosyl and 1-(2‘-Deoxy-2‘-fluoro-β-d-2‘-ribofuranosyl) Pyrimidine Nucleoside Analogs

Abstract: The resurgence of tuberculosis and the emergence of multiple-drug-resistant strains of Mycobacteria necessitate the search for new classes of antimycobacterial agents. We synthesized a series of 1-beta-D-2'-arabinofuranosyl and 1-(2'-deoxy-2'-fluoro-beta-D-ribofuranosyl) pyrimidine nucleosides possessing diverse sets of alkynyl, alkenyl, alkyl, and halo substituents at the C-5 position of the uracil and investigated their effect on activity against M. tuberculosis, M. bovis, and M. avium. Among these molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 42 publications
(113 reference statements)
4
42
0
Order By: Relevance
“…This implies that unsaturation of the aliphatic side chain is an essential structural feature for the in vitro antimycobacterial activity. This is further supported by recent findings which revealed that the aliphatic side chain, such as alkyl, alkenyl and alkynyl at position-5 of uracil significantly contributes to the antimycobacterial activity of pyrimidine nucleosides on M. tuberculosis 11 . To further explore the effect of degree of unsaturation on the antimycobacterial properties, methyl ketones having two carbon–carbon double bonds were synthesized and incorporated into the alkaloid.…”
Section: Resultssupporting
confidence: 56%
“…This implies that unsaturation of the aliphatic side chain is an essential structural feature for the in vitro antimycobacterial activity. This is further supported by recent findings which revealed that the aliphatic side chain, such as alkyl, alkenyl and alkynyl at position-5 of uracil significantly contributes to the antimycobacterial activity of pyrimidine nucleosides on M. tuberculosis 11 . To further explore the effect of degree of unsaturation on the antimycobacterial properties, methyl ketones having two carbon–carbon double bonds were synthesized and incorporated into the alkaloid.…”
Section: Resultssupporting
confidence: 56%
“…We designed, synthesized and examined a variety of known and unknown pyrimidine nucleosides substituted/unsubstituted at 2-, 4-, 5- and/or 6- positions of the base, and containing various deoxyribose, ribose, arabinose, dideoxyribose and acyclic sugar moieties. We found that 5-alkynyl substituted pyrimidine nucleosides demonstrated the most potent activity against mycobacteria [52,53]. The MIC 90 exhibited by compounds of this series ( 2 , 3 and 4 , Figure 2) was in the range of 1–5 μg/mL) against Mtb H37Ra.…”
Section: Drug Discovery Programmentioning
confidence: 98%
“…Johar and co-workers described the synthesis of 1-β-D-arabinofuranosyl-5-(1-methoxy-2-iodoethyl)uracil ( 79 ) (Scheme 11) in a recent article [19]. The compound was also reported by Kumar and co-workers in 1992 [20].…”
Section: Reviewmentioning
confidence: 94%